Sequential Targeting of CD52 and TNF Allows Early Minimization Therapy in Kidney Transplantation: From a Biomarker to Targeting in a Proof-Of-Concept Trial - Viklicky, Ondrej; Hruba, Petra; Tomiuk, Stefan; Schmitz, Sabrina; Gerstmayer, Bernhard; Sawitzki, Birgit; Miqueu, Patrick; Mrázová, Petra; Tycova, Irena; Svobodova, Eva; Honsova, Eva; Janssen, Uwe; et al. (PLoS One, 2017)
BACKGROUND: There is high medical need for safe long-term immunosuppression monotherapy in kidney transplantation. Selective targeting of post-transplant alloantigen-(re)activated effector-T cells by anti-TNF antibodies after global T cell depletion may allow safe drug minimization, however, it is unsolved what might be the best maintenance monotherapy. METHODS: In this open, prospective observational single-centre trial, 20 primary deceased donor kidney transplant recipients received 2x20 mg Alemtuzumab (d0/d1) followed by 5 mg/kg Infliximab (d2). For 14 days all patients received only tacrolimus, then they were allocated to either receive tacrolimus (TAC, n = 13) or sirolimus (SIR, n = 7) monotherapy, respectively. Protocol biopsies and extensive immune monitoring were performed and patients were followed-up for 60 months. RESULTS: TAC-monotherapy resulted in excellent graft survival (5yr 92%, 95%CI: 56.6-98.9) and function, normal histology, and no proteinuria. Immune monitoring revealed low intragraft inflammation (urinary IP-10) and hints for the development of operational tolerance signature in the TAC- but not SIR-group. Remarkably, the TAC-monotherapy was successful in all five presensitized (ELISPOT+) patients. However, recruitment into SIR-arm was stopped (after n = 7) because of high incidence of proteinuria and acute/chronic rejection in biopsies. No opportunistic infections occurred during follow-up. CONCLUSIONS: In conclusion, our novel fast-track TAC-monotherapy protocol is likely to be safe and preliminary results indicated an excellent 5-year outcome, however, a full-scale study will be needed to confirm our findings. TRIAL REGISTRATION: EudraCT Number: 2006-003110-18.
Keywords: Antigens, CD; CD antigeny; Humans; lidé středního věku; Graft Rejection; Female; mladý dospělý; dospělí; Sirolimus; sirolimus; lidé; Biomarkers; Antigens, Neoplasm; imunosupresiva; antigeny nádorové; TNF-alfa; Adult; Immunosuppressive Agents; glykoproteiny; transplantace ledvin; biologické markery; ženské pohlaví; monitorování imunologické; Male; Glycoproteins; Middle Aged; stanovení celkové genové exprese; Monitoring, Immunologic; Tacrolimus; Kidney Transplantation; Young Adult; Tumor Necrosis Factor-alpha; takrolimus; Gene Expression Profiling; mužské pohlaví; prospektivní studie; rejekce štěpu; Prospective Studies